Imaginarios y marcos valorativos de funcionarios de justicia sobre víctimas de violación sexual en Cali - Victoria Morales , María Irene (2022)
This paper forms part of a more extensive research project called “From victims to survivors and living persons: integral attention in cases of sexual violation”, developed in Cali, Colombia. The study enquires about the needs of female victims/survivors of sexual violence, and discusses the role of the judicial officials in the process of accusation. The problematization of this situation is aimed at the transformation of services in law enforcement institutions. The paper analyses a series of accusations relating to rape in 25 proceedings from 2000 to 2003, all of them cold cases. Semantic fields, apparently invisible to the official during the reporting process, are exposed. Two conclusions are drawn: first, that stereotypes and prejudices held by judicial officials about the victim affect mediation even before the accuser is given recognition as a victim. Second, that instrumentalization of victims in order to obtain evidence is a dehumanizing procedure, as it may induce self-guilt, shame and a second victimization.